2015
DOI: 10.5194/gmd-8-2967-2015
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of the integral invariant coordinates <I>I</I> and <I>L</I>* in the magnetosphere and mapping of the regions where <I>I</I> is conserved, using a particle tracer (ptr3D v2.0), LANL*, SPENVIS, and IRBEM

Abstract: Abstract. The integral invariant coordinate I and Roederer's L or L * are proxies for the second and third adiabatic invariants, respectively, that characterize charged particle motion in a magnetic field. Their usefulness lies in the fact that they are expressed in more instructive ways than their counterparts: I is equivalent to the path length of the particle motion between two mirror points, whereas L * , although dimensionless, is equivalent to the distance from the center of the Earth to the equatorial p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…The structures examined in these studies were observed in the near-Earth plasma sheet or in the mid-tail, i.e., in regions where the H + motion may be regarded as adiabatic (i.e., κ > 3). Dispersion structures in these studies likely follow from violation of the second adiabatic invariant (associated with bouncing motion along the field line) during dipolarization, this latter invariant being otherwise conserved in steady state (e.g., Konstantinidis and Sarris, 2015). In contrast, the structure portrayed in Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The structures examined in these studies were observed in the near-Earth plasma sheet or in the mid-tail, i.e., in regions where the H + motion may be regarded as adiabatic (i.e., κ > 3). Dispersion structures in these studies likely follow from violation of the second adiabatic invariant (associated with bouncing motion along the field line) during dipolarization, this latter invariant being otherwise conserved in steady state (e.g., Konstantinidis and Sarris, 2015). In contrast, the structure portrayed in Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The role of this maximum L ∗ value, or last closed drift shell (LCDS), has been explored by Xiang et al () and Olifer et al (). LCDS values have also been considered for protons by Kostantinidis and Sarris ().…”
Section: Introductionmentioning
confidence: 99%
“…In Konstantinidis & Sarris (2015), magnetic field models were compared through the analysis of L * vs increasing distances into the tail. The authors of this work report differences in adiabatic invariants between various empirical model tools, with variations in L * as much as 5% at 6 R E and 30% at 8 R E .…”
Section: Dependence Of Invariants On Magnetic Field Modelmentioning
confidence: 99%